Subjective well-being among PhD students in mainland China: the roles of psychological capital and academic engagement - Cao, Fei; Zhang, Li-fang; Li, Mengting; Xie, Zhengli (Frontiers in Psychology, 2024)
The mental well-being of PhD students is a major concern in higher education. However, very few studies have investigated the influencing factors of PhD students' subjective well-being (SWB) -an important indicator of mental well-being. Even no study on the influencing factors of PhD students' SWB has been undertaken in mainland China. Based on job demands-resources theory, the present study pioneers the investigation of the relationship between PhD students' psychological capital (PsyCap; comprising self-efficacy, hope, resilience, and optimism) and SWB (comprising positive affect, negative affect, and life satisfaction) in mainland China. It further examined the mediating role of academic engagement (comprising vigor, dedication, and absorption) in this relationship. PhD students (n = 376) from two comprehensive universities in Jiangsu province responded to an online survey. The results showed that (1) self-efficacy was positively associated with life satisfaction, hope was positively associated with positive affect, optimism was significantly associated with all three dimensions of SWB, but resilience was not significantly associated with any of the three SWB dimensions; and (2) dedication mediated the relationship between hope and life satisfaction and that between optimism and negative affect and life satisfaction, but vigor and absorption did not mediate any of the PsyCap-SWB relationships. Limitations and practical implications of this study are discussed.